2024
DOI: 10.1039/d3mh02090h
|View full text |Cite
|
Sign up to set email alerts
|

In situ self-reconstructed hierarchical bimetallic oxyhydroxide nanosheets of metallic sulfides for high-efficiency electrochemical water splitting

Yaning Fan,
Junjun Zhang,
Jie Han
et al.

Abstract: The advancement of economically efficient electrocatalysts for alkaline water oxidation based on transition metals is essential to attain hydrogen production through water electrolysis. In this investigation, a straightforward one-step solvent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In multiple metal materials, especially for HEMs, the metallic electronic interaction may increase the oxidation state of one key element, enhance the covalency of the M–O bond, activate lattice oxygen and even widen the d-band for efficient adsorption modulation. 64–67 The HEMs may be excellent candidates for catalyzing OER by microscopic mechanism optimization.…”
Section: Fundamentals and Bottleneck Of Electrochemical Water Splittingmentioning
confidence: 99%
“…In multiple metal materials, especially for HEMs, the metallic electronic interaction may increase the oxidation state of one key element, enhance the covalency of the M–O bond, activate lattice oxygen and even widen the d-band for efficient adsorption modulation. 64–67 The HEMs may be excellent candidates for catalyzing OER by microscopic mechanism optimization.…”
Section: Fundamentals and Bottleneck Of Electrochemical Water Splittingmentioning
confidence: 99%
“…Recent studies have shown that one of the key factors affecting the catalytic efficiency of palladium-based nanocatalysts is the catalytic active site on the catalyst surface, and the catalytic efficiency of palladium-based catalysts can be greatly improved by constructing abundant catalytic active sites . The introduction of defects in palladium-based nanocatalysts is the most direct way to construct catalytic active sites. And among the different types of defects introduced, interfacial defects in the construction of heterogeneous structures show unique advantages. The palladium atoms at interfacial defects have more uncoordinated bonds and high surface energy, which can effectively strengthen the interaction between palladium atoms and alcohol molecules so that alcohol molecules are more easily adsorbed on the surface of palladium atoms, thus improving the catalytic efficiency. , However, at present, the conditions for constructing such multiphase interfacial palladium-based catalysts are harsh, and the steps are complicated. Furthermore, the synthesized multiphase structures have poor controllability.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of industrialization and the acceleration of urbanization, the concentration of carbon dioxide (CO 2 ) in the earth's atmosphere is increasing rapidly, causing the deterioration of the environment and ecology. 1–10 The conversion of CO 2 into valuable chemical fuels through electrochemistry can benefit from being powered by green electricity and is easy to modularize and scale up, and is regarded as one of the most promising technologies for carbon neutrality. 11–14 Catalysts as the core of the CO 2 RR have been extensively studied, and multiple catalysts have been designed to achieve different products, such as CO, 15 formate, 16 ethanol, 17 and ethylene.…”
Section: Introductionmentioning
confidence: 99%